Inventarisation of Parasite in ”Dumbo” Catfish Clarias sp. from Bogor Region - Hadiroseyani, Y.; Hariyadi, P.; Nuryati, Sri (Indonesian Society of Scientific Aquaculture (ISSA), 2006)
Outbreak of parasites can reduce aquaculture productivity or even cause mass mortality of fish. Few quantities of parasite infection may still be tolerated by the host, however high intensity of infection can impair to fish metabolism or even damage of organelle. Proper treatment can be done when parasite infecting fish is known. This study was conducted to record parasite infecting